2021
DOI: 10.29008/etc2021-693
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic investigation of an open 3D steam turbine test case and blade shape optimization with improved flutter behavior

Abstract: The paper describes the flutter stability assessment of a steam turbine rotor and the application of a multi-disciplinary shape optimization procedure to obtain a new blade geometry with higher efficiency and an improved flutter stability. The investigated test case consists of a steam turbine last stage representative of modern industrial steam turbine blading, firstly presented by Durham University and intensively investigated during last years. The aerodamping results on the original geometry, obtained by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…The overall results were deemed to be in good agreement with (Qi et al, 2017) using the flow solver LUFT. (Pinelli et al, 2021) used non-linear method to obtain the aerodynamic damping and found good agreement with previous studies. An aeromechanical optimization workflow is established, and aerodynamic/aeromechanical performance of the optimum blade profile is compared to the baseline geometry.…”
Section: Introductionsupporting
confidence: 80%
“…The overall results were deemed to be in good agreement with (Qi et al, 2017) using the flow solver LUFT. (Pinelli et al, 2021) used non-linear method to obtain the aerodynamic damping and found good agreement with previous studies. An aeromechanical optimization workflow is established, and aerodynamic/aeromechanical performance of the optimum blade profile is compared to the baseline geometry.…”
Section: Introductionsupporting
confidence: 80%